PENGARUH KUALITAS KEHIDUPAN KERJA TERHADAP KOMITMEN ORGANISASIONAL PADA PT. HASJRAT ABADI MANADO - FRIENDLY FRISKI KAUNANG; Riane J. Pio; Mieke Roring (Universitas Sam Ratulangi, 2017)
The automotive sector is one of the sectors that contribute to the economic growth ofIndonesia. Job creation from the automotive sector is one of the solutions for the government inaddressing the problem of unemployment. On the hand the company in the automotive sector canachieve its goal of obtaining maximum profit. By earning the maximum profit of owners andcapital for the company’s operations can increase. Quality of work life is determined by thecompensation received by employees, the opportunity to participate in the organization, jobsecurity, work design, and the quality of interaction among members of the organization. Thepsychological dynamics of the quality of work life with organizational commitment is when thequality of working life of an employee is good then the organizational commitment will be high.Conversely, if the quality of working life is low then the organization's commitment will also below, causing a turnover in the organization. The purpose of this study is to determine whether thequality of work life has a significant effect on organizational commitment. Technical dataanalysis used in this study is the validity and reliability test questionnaire research, simple linearregression analysis and hypothesis t test. The population in this study were all employees of PTHasjrat Abadi branch of Manado which amounted to 138 people and the sample obtained byusing slovin formula and obtained as many as 58 respondents. Human as labor is the core orasset of every company, because man will be the one who will determine the role of otherresources that are included in the production process. The results showed that the quality of worklife positively affect the organizational commitment at PT Hasjrat Abadi Branch Manado andquality of work life significantly influence the organizational commitment at PT Hasjrat AbadiBranch Manado. In this studied only limited to the influence of quality of work life toorganizational commitment while other factors that also affect the organizational commitmentthat has not bee revealed how much influence. Hopefully in the next research can discuss otherfactors that have not been studied in this study.Keywords: Quality Of Work Life, Organizational Commitment